PprI: The Key Protein in Response to DNA Damage in Deinococcus - Lu, Huizhi; Hua, Yuejin (Frontiers in Cell and Developmental Biology, 2021)
Deoxyribonucleic acid (DNA) damage response (DDR) pathways are essential for maintaining the integrity of the genome when destabilized by various damaging events, such as ionizing radiation, ultraviolet light, chemical or oxidative stress, and DNA replication errors. The PprI–DdrO system is a newly identified pathway responsible for the DNA damage response in Deinococcus, in which PprI (also called IrrE) acts as a crucial component mediating the extreme resistance of these bacteria. This review describes studies about PprI sequence conservation, regulatory function, structural characteristics, biochemical activity, and hypothetical activation mechanisms as well as potential applications.